Uptake and action of a disulphonic stilbene (SITS) in the perfused guinea-pig liver: a comparison with bromsulphthalein. - Rutishauser, S C (1983)
1. Livers were perfused with a Krebs-Ringer bicarbonate buffer in a single-pass perfusion system. Bile secretion was maintained by infusion of secretin. 4-Acetamido-4'-isothiocyano-2,2'-stilbene disulphonic acid (SITS) was added to the perfusate to give concentrations ranging between 5 x 10(-6) and 10(-4) M. 2. SITS was extracted from the perfusate by the liver (V, 0 . 15 mumol/min per g liver; Km 8 . 6 x 10(-5) M) and excreted in bile in a modified form (bile/plasma ratio: 50-170; maximum rate of excretion: 25 nmol/min per g liver wet wt). 3. The rates of uptake and excretion of bromsulphthalein (BSP) were similar to those for SITS, with the exception that the affinity of BSP for hepatic uptake was greater (Km 1 . 8 x 10(-5) M). 4. Both SITS and BSP decreased the rate of bile flow. A 50% reduction in bile flow was attained in each case at an estimated drug content of the liver of 1 . 5 mumol/g wet wt. 5. Unlike other cells the hepatocyte appears to be readily penetrated by SITS, and it is suggested that SITS inhibits bile secretion by inhibiting an intracellular mechanism which could be mitochondrial in location.